Challenging symbolic violence and hegemony in music education through contemporary pedagogical approaches. Issue 6 (2nd November 2017) - Powell, Bryan; Smith, Gareth Dylan; D'Amore, Abigail
ABSTRACT: Music education takes place in socio-political systems that institutionalise cultural hegemony and social stratification through perpetuating symbolically violent practices and unconscious assumptions regarding the purpose of music and music education in society. Education systems serve to perpetuate class divisions and structures, excluding the music and aspirations of many people through the imposition of an increasingly neoliberal ideology. This article discusses the pedagogical approaches of Musical Futures and Little Kids Rock, and their orientations to democratising learning in the school music classroom through incorporation of practices and perspectives in making and learning popular music, focussed around learner-led teaching and learning.